(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Women entrepreneurship is seen as central to the growth of economic development, social justice and the generation of innovation everywhere. When women commence businesses they get to open up employment opportunities, lessen the rate of poverty, and help in the eradication of the poor standards of social justice for other vulnerable groups. Female owners show lots of determination and ingenuity, and start in various fields from technology, manufacture, services, and social innovations. Nonetheless, similar as men, women have certain issues such as gender discrimination, less access to financial capital, little access to coaching, and expectations concerning work-life balance. Such barriers are further compounded by culture, law, and real Discriminations more so in developing economies. Through this paper , it will look at progress in women entrepreneurial ventures and discuss patterns, drivers of success and some of the challenges that women entrepreneurs face. Through education and technological advancement they breakdown barriers of the past women and engage global markets. In addition, the paper examines the need for policy measures including, gender sensitive funding instruments, entrepreneurship development, and institutional support to support an enabling entrepreneurial environment.